1990
DOI: 10.1093/ajcn/52.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of free-living energy expenditure by the doubly labeled water method and heart-rate monitoring

Abstract: Total energy expenditure (TEE) was measured simultaneously in 14 free-living adults over 15 d by the doubly labeled water (DLW) method and for 2-4 separate days by heart-rate (HR) monitoring. Individual curves for HR vs oxygen consumption (VO2) were obtained and an HR (FLEX HR: 97 +/- 8 beats/min, range 84-113 beats/min) that discriminated between rest and activity was identified. Calibration curves were used to assign an energy value to daytime HR above FLEX HR. Below FLEX HR energy expenditure was taken as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
132
2
4

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 12 publications
11
132
2
4
Order By: Relevance
“…In the original studies (Livingstone et al, 1990a(Livingstone et al, , 1992a, EE HR and EE DLW showed good agreement at the group level, but individual estimates of EE HR ranged from 722 to þ 52% of corresponding EE DLW values. The reasons for these discrepancies have been discussed in detail in the source references (Livingstone et al, 1990a(Livingstone et al, , 1992a) and include limited sampling periods for the estimation of HR EE , inappropriate Flex-HR definition and=or unrepresentative calibration data. In particular, it is most unlikely that 2 -4 days of EE HR , as was measured in these subjects, would provide a representative estimate of habitual EE HR .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the original studies (Livingstone et al, 1990a(Livingstone et al, , 1992a, EE HR and EE DLW showed good agreement at the group level, but individual estimates of EE HR ranged from 722 to þ 52% of corresponding EE DLW values. The reasons for these discrepancies have been discussed in detail in the source references (Livingstone et al, 1990a(Livingstone et al, , 1992a) and include limited sampling periods for the estimation of HR EE , inappropriate Flex-HR definition and=or unrepresentative calibration data. In particular, it is most unlikely that 2 -4 days of EE HR , as was measured in these subjects, would provide a representative estimate of habitual EE HR .…”
Section: Discussionmentioning
confidence: 94%
“…The loss of sensitivity for screening EI WR can be largely attributed to the higher within-subject coefficient of variation in the measurements of EE by HR monitoring (13.3, 17.6, 11.2% for the total group, adults and children respectively) relative to DLW, which was taken as 8.2% (Black & Cole, 2000). In the original studies (Livingstone et al, 1990a(Livingstone et al, , 1992a, EE HR and EE DLW showed good agreement at the group level, but individual estimates of EE HR ranged from 722 to þ 52% of corresponding EE DLW values. The reasons for these discrepancies have been discussed in detail in the source references (Livingstone et al, 1990a(Livingstone et al, , 1992a) and include limited sampling periods for the estimation of HR EE , inappropriate Flex-HR definition and=or unrepresentative calibration data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This HRFlex method has previously been validated against whole-body calorimetry (Spurr et al, 1988;Ceesay et al, 1989) and against doubly-labelled water (Livingstone et al, 1990;Lovelady et al, 1993). This technique provides an objective and accurate estimate of EE at a group level, as well as providing a means of describing the pattern of physical activity (Wareham et al, 1997).…”
Section: Introductionmentioning
confidence: 99%